Does anxiety have an impact on temporomandibular disorders? A study in a Turkish sample by using specific questionnaires - Akbulut, Aslıhan; Kurt, Hanefi; Uslu Toygar, Hilal; Yıldırım, Erol (Taylor and Francis Ltd., 2024)
Objective: The aim of the study is to verify the impact of anxiety on temporomandibular disorders (TMD) by using specific questionnaires in a Turkish sample. Methods: This survey was conducted on 292 patients with a mean age of 38.59 ± 10.38 using Helkimo index, Oral Health Impact Profile (OHIP-14), and State Trait Anxiety Inventory (STAI). Spearman Correlation and Fisher Freeman Halton analyses were used for the statistical analysis. Results: There was no statistically significant difference between the Helkimo anamnestic dysfunction (HAD) levels in terms of OHIP-14 total scores or STAI state scores. There was, however, a statistically positive correlation between STAI state and OHIP-14 total values at 18.4%, a positive correlation between the STAI trait and OHIP-14 total values at 29.8%. Conclusion: No significant correlation was observed between OHIP-14 total scores, STAI state scores, and HAD levels. Therefore, this study did not find a significant relationship between TMDs and anxiety. © 2022 Taylor & Francis Group, LLC.
Keywords: Helkimo Index; Oral Health Impact Profile; State-Trait Anxiety Inventory; Temporomandibular Disorder